2011
DOI: 10.1007/s00044-011-9606-4
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of some pyrazole derivatives of expected anti-inflammatory and analgesic activities

Abstract: Design and synthesis of some pyrazole derivatives 4-11 of expected anti-inflammatory and analgesic activities. In addition, docking of the tested compounds into cyclooxygenase II using (MOE) was performed to rationalize the obtained biological results and their mechanism of action. The structures of the new compounds were elucidated by spectral and elemental analyses. All the newly synthesized compounds were evaluated for their anti-inflammatory activity using the carrageenan-induced rat paw edema method. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…They are inhibitors and deactivators of liver alcohol dehydrogenase [17]. The 3,5-substituted pyrazoles show hypoglycemic activity [13] in glucose primed and diabetic rats. Heterocyclic compounds are also used as intermediaries in the industry of the dyes [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are inhibitors and deactivators of liver alcohol dehydrogenase [17]. The 3,5-substituted pyrazoles show hypoglycemic activity [13] in glucose primed and diabetic rats. Heterocyclic compounds are also used as intermediaries in the industry of the dyes [18].…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazoles are one of the most important classes of heterocyclic compounds and they are very significant for medicinal chemistry [10]. Pyrazoles exhibit antiarrhythmic [11], antipyretic [12], analgesic and anti-inflammatory [13], neuroleptic [14], sedative-hypnotic effect [15] and antimicrobial activity [16]. They are inhibitors and deactivators of liver alcohol dehydrogenase [17].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Additionally, many studies proved different activities of pyrazoline derivatives as receptor tyrosine kinase, topoisomerase 1, carbonic anhydrase and cholinesterase inhibitors. It was found that nitrogen atoms of the pyrazoline ring and at least one substitution with aryl moiety are essential for anti-inflammatory activity (Gawad et al, 2012). [11][12][13][14][15] Several drug molecules carrying pyrazole core with different activities are currently available in the market, for example, antipyrine (analgesic), celecoxib (anti-inflammatory), pyrazofurin (antibiotic).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that nitrogen atoms of the pyrazoline ring and at least one substitution with aryl moiety are essential for anti-inflammatory activity (Gawad et al, 2012). [11][12][13][14][15] Several drug molecules carrying pyrazole core with different activities are currently available in the market, for example, antipyrine (analgesic), celecoxib (anti-inflammatory), pyrazofurin (antibiotic). 16 It is known that fluorine substitution increases biological activity and metabolic-chemical stability (compared to C-H bond) in drug research.…”
Section: Introductionmentioning
confidence: 99%
“…The plenteous literature affirms the ubiquitous nature of aza-heterocyclic compounds especially the pyrazole derivatives. They are documented to possess anti-inflammatory [4][5][6][7], antibacterial, antifungal [8][9][10][11], antiviral [12,13], antimalarial [14,15], analgesic [16][17][18], antipyretic [19,20], antidepressant [21][22][23], anticonvulsant [24,25], antidiabetic [26,27], antiangio-genetic [28], antitubercular [29] and anticancer [30][31][32][33] activities.…”
Section: Introductionmentioning
confidence: 99%